The study of abdominal trauma: non operative and operative intervention and their outcome - Ramanuj, Avadhesh M.; Panchal, Hemang A. (International Surgery Journal, 2016)
Background:The aim was to study the cases of abdominal trauma in context of surgical intervention and criteria for non-operative and operative management, post-operative morbidity, mortality and final outcome. Methods: The study of 50 cases of abdominal trauma, including blunt as well as penetrating trauma was conducted prospectively during the period of 23 months (January 2010 to November 2011). Patients of all age and sex who were admitted in our department after abdominal trauma were potential candidate for enrolment in this study and study was done in context to fulfill our aim. Results:In our study, 4 (8%) patients had undergone conservative management while 46 (92%) patients were managed by operative intervention. Amongst the surgical procedures drainage of haemoperitoneum and haemostasis (n = 20, 43.47%) is commonly done procedure for abdominal trauma involving solid organs especially liver. However some splenic injury may warrant removal of spleen (n = 10, 21.79%). In small bowel perforation primary repair (n = 8, 17.39%) is the choice of procedure however resection anastomosis (n = 4, 08.69%) is necessary if multiple perforations are present in small segment. Post-operative recovery in this study was generally good with rate of complication as 8% (n = 4) and most of the complications were wound related (n = 04, 08%). we have observed mortality rate of 8% (n = 04) and persistent shock and haemorrhage (n = 3, 75%) is the most common cause of death in our study. The reason was extensive polytrauma involving massive injuries of spleen, liver, pancreas and kidney associated with thoracic injuries, orthopaedic injuries and cranio-cerebral injuries. The average hospital stay in our study was 9.26 days. Out of 50 abdominal trauma patients 46 (92%) has survived and shown good prognosis on follow ups. These data suggests that good outcome can be achieved if proper evaluation done and timely definitive treatment is given to the trauma victims. Conclusions:From our study we can conclude that for “optimum outcome” of abdominal trauma through timely definitive treatment is of prime importance. Establishment of dedicated and efficient trauma care system is mandatory to achieve these goals in abdominal trauma management.